(untitled) (Journal of the College of Basic Education, 2022)
University education is one of the main pillars in society, and the effectiveness of the university educational organization is mainly due to the loyalty to the university among the teachers, their commitment to values, and their endeavor to make efforts in favor of achieving the goals of the university.